Analisis Kejadian Stunting Pada Balita Usia 24–59 Bulan di Wilayah Kerja Puskesmas Mariana Kabupaten Banyuasin Tahun 2023 - Ade Kurnia Asih; Arie Wahyudi; Syntia Rahutami (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
In 2020, it is estimated that the number of stunted sufferers under the age of five will be 149.2 million or reach 22% in 2020. This figure has increased from the previous year, namely in 2018 there were around 162 million children under five or 21.9% and in 2019 there were 21.3% or as many as 144 million children under five in the world were stunted. This study aims to analyze the incidence of stunting in toddlers aged 24–59 months in the working area of ??the Mariana Health Center, Banyuasin Regency in 2023. The research design used is descriptive analytic with cross sectional method. Sampling using purposive sampling technique involving 97 respondents. Research data collection using a questionnaire. Research analysis with chi square test. The results showed that complementary breastfeeding (p = 0.027), co-morbidities (p = 0.012), smoking habits (p = 0.011) had a relationship with the incidence of stunting in toddlers aged 24-59 months. It is hoped that health workers will provide education about proper, appropriate and varied complementary breastfeeding to toddlers starting at the age of 6 months to 23 months in Posyandu and toddler mother classes.